Working towards a better understanding of type 2 diabetes care organization with First Nations communities: a qualitative assessment - Lisa A. Wozniak; Jeffrey A. Johnson; Dean T. Eurich (BMC, 2020)
Abstract Background Diabetes care is suboptimal in First Nations populations. Innovative and culturally-relevant approaches are needed to promote proactive organization of diabetes care for diabetes patients on-reserve in Canada. The Reorganizing the Approach to Diabetes care through the Application of Registries (RADAR) model is one strategy to improve care: an integrated disease registry and electronic health record for community healthcare workers with centralized care coordination. The aim of this study was to qualitatively assess the organization of type 2 diabetes care in participating communities in Alberta, Canada, at baseline prior to implementing RADAR. Methods Using qualitative description, we purposefully sampled healthcare workers involved in diabetes care at each health center. We used the 5Rs framework (i.e., Recognize, Register, Resource, Relay, Recall) to inform the baseline assessment and conducted group interviews in 6 communities with 16 healthcare workers. Detailed notes were taken and validated by participants. Data was managed using ATLAS.ti 8 and analyzed using content analysis. Results We found strong commitment and effort by local healthcare workers to support people living with type 2 diabetes in their communities. However, healthcare workers were limited in their ability to identify (i.e., recognize), track (i.e., register and relay) and manage (i.e., resource and recall) people with type 2 diabetes as proposed by the 5Rs framework. The organization of diabetes care was often reactive and dependent on patients' abilities to navigate the health system. Interestingly, participants talked about the 5Rs in relationship to one another, not in a linear or isolated manner. Conclusions Overall, the organization of diabetes care in participating communities did not align with the recommended approach of the 5Rs framework. In addition, we propose "reimagining" the 5Rs to reflect the interdependence and mediation of components situated within human and financial resources. This will better equip healthcare workers to assess, plan and execute organized and proactive diabetes care. However, the onus on people living with type 2 diabetes to engage with healthcare services remains a concern. Trial registration ISRCTN.com, ISRCTN14359671.